2009
DOI: 10.1016/j.vetmic.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity of probiotics—Oxalate degradation

Abstract: 24Urinary tract stones are an important clinical problem in human and veterinary 25 medicine. Hyperoxaluria is the single strongest promoter of kidney stone formation. The 26 aims of the present study were to, (a) evaluate oxalate degradation by a range of 27Bifidobacteria species and Lactobacillus species isolated from the canine and feline 28 gastrointestinal tract in vitro and, (b) to determine the impact of oxalate degradation by 29 selected strains in vivo. The bacteria were grown in oxalate-containing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…However, in vitro analysis of oxalate degradation revealed that only half of the Lactobacillus isolates actually degraded oxalate under the given conditions. Consistent with previous reports, there were significant differences between isolates within some OTUs in regard to oxalate degradation (34,51). The difference between potential activity indicated by the presence of the oxc gene and actual activity quantified in the assays underscores the role of the environment in mediating oxalate degradation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in vitro analysis of oxalate degradation revealed that only half of the Lactobacillus isolates actually degraded oxalate under the given conditions. Consistent with previous reports, there were significant differences between isolates within some OTUs in regard to oxalate degradation (34,51). The difference between potential activity indicated by the presence of the oxc gene and actual activity quantified in the assays underscores the role of the environment in mediating oxalate degradation.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have implicated the Lactobacillus genus as a potentially important contributor to oxalate degradation in the mammalian gut (34,51). The results of this study suggest that lactobacilli are the primary oxalate-degrading bacteria present in N. albigula.…”
Section: Discussionmentioning
confidence: 49%
“…Previous research has focused on the role of individual taxa in oxalate degradation (7,20,29,37,38). However, several oxalate-degrading taxa have now been identified from the mammalian gut, and other taxa may be affected by oxalate in obscure ways (20,26,39,40). To address the gaps, we combined controlled laboratory diet trials, physiological assays, and microbial ecology to examine the taxonomic and functional response of the whole gut microbiota in a mammalian herbivore, N. albigula, which naturally consumes large amounts of oxalate in its diet, a simple compound that is metabolized exclusively by the gut microbiota (18,26).…”
Section: Discussionmentioning
confidence: 99%
“…Photocatalytic, ultrasonic, and biochemical methods for destroying oxalic acid have all been studied [14][15][16]. However, the reagent cost, energy consumption, and treating periods all limit the efficiency of degradation [17].…”
Section: Introductionmentioning
confidence: 99%